2000
DOI: 10.1084/jem.191.9.1525
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Transcription Factor Rfx5 during the Inhibition of Both Constitutive and Interferon γ–Inducible Major Histocompatibility Complex Class I Expression in Chlamydia-Infected Cells

Abstract: We have previously shown that the obligate intracellular pathogen chlamydia can suppress interferon (IFN)-γ–inducible major histocompatibility complex (MHC) class II expression in infected cells by degrading upstream stimulation factor (USF)-1. We now report that chlamydia can also inhibit both constitutive and IFN-γ–inducible MHC class I expression in the infected cells. The inhibition of MHC class I molecule expression correlates well with degradation of RFX5, an essential downstream transcription factor req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
202
4
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 50 publications
2
202
4
1
Order By: Relevance
“…In addition to cyclin B1, several other host proteins have been reported to undergo proteolytic cleavage in response to C. trachomatis infection (8,9,12,41,45,46). Degradation of the transcription factors RFX5 and USF-1 during C. trachomatis infection has been shown to reduce expression of the major histocompatibility complex genes and thereby serve as a putative immune evasion strategy (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cyclin B1, several other host proteins have been reported to undergo proteolytic cleavage in response to C. trachomatis infection (8,9,12,41,45,46). Degradation of the transcription factors RFX5 and USF-1 during C. trachomatis infection has been shown to reduce expression of the major histocompatibility complex genes and thereby serve as a putative immune evasion strategy (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of the transcription factors RFX5 and USF-1 during C. trachomatis infection has been shown to reduce expression of the major histocompatibility complex genes and thereby serve as a putative immune evasion strategy (45,46). Likewise, degradation of the BH3 (Bcl-2 homology domain 3) family of proapoptotic factors protects C. trachomatis-infected cells from programmed cell death (8,12,41).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to note that chlamydia alters a variety of host cell responses, including proinflammatory cytokine and chemokine secretion (22), inhibition of apoptosis (39), and inhibition of IFN-␥-inducible MHC class I and II expression (38,40). Chlamydiainduced immune evasion mechanisms may allow the microbe to escape immune surveillance, especially at early stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that chlamydia-laden vacuoles can actively avoid fusion with lysosomes, although the molecular mechanism involved remains to be elucidated (21,42). We have previously shown that chlamydiae possess various molecular means for protecting the infected cells from being destroyed by host defense mechanisms, including suppression of host cell major histocompatibility complex antigen expression (52)(53)(54) and blockade of host cell apoptosis pathways (16). However, due to the complex interactions between chlamydiae and host cells, different labs have reported varied outcomes in regard to chlamydial effects on the host apoptosis program.…”
mentioning
confidence: 99%